2012
DOI: 10.1166/msr.2012.1008
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Adenine Dinucleotide 2 -Phosphate (NAADP) Binding Proteins in T-Lymphocytes

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is a messenger that regulates calcium release from intracellular acidic stores. Although several channels, including two-pore channels (TPC), ryanodine receptor (RYR) and mucolipin (TRP-ML1) have been implicated in NAADP regulation of calcium signaling, the NAADP receptor has not been identified. In this study, the photoaffinity probe, [32P]–5-azido-NAADP ([32P]–5-N3-NAADP), was used to study NAADP binding proteins in extracts from NAADP responsive Jurkat T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
(67 reference statements)
4
40
0
Order By: Relevance
“…1C and D). This result under- scores prior conclusions (11)(12)(13). Repetition of our published photolabeling experiments with Tpcn1 T159 samples characterized by Ruas and colleagues (15) is expected to yield a similar result.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…1C and D). This result under- scores prior conclusions (11)(12)(13). Repetition of our published photolabeling experiments with Tpcn1 T159 samples characterized by Ruas and colleagues (15) is expected to yield a similar result.…”
supporting
confidence: 77%
“…Photolabeling studies using a radioactive NAADP-derived probe (5N 3 -[ 32 P]NAADP) have suggested that NAADP may not directly bind to TPCs but may stimulate channel activity via small NAADP-binding proteins (ϳ23 kDa) associated with the TPC complex (11)(12)(13)(14). One piece of evidence supporting this idea is the preservation of photolabeling in TPC knockout mice (11).…”
mentioning
confidence: 99%
“…However, it is important to note that the Ca 2+ release studies are done in cellular homogenates of sea urchin eggs and with intact cells for the mammalian receptor. Recently, photoaffinity labeling of NAADP targets in homogenates of sea urchin eggs and of the mammalian cell lines SKBR3 and Jurkat showed different molecular masses of the photolabeled proteins [32, 46, 47]. This suggests that differences are inherent in the receptors themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, insensitivity of TPCs to NAADP might reflect loss of crucial accessory factors. In this context, photo-affinity labeling studies suggest that NAADP does not bind directly to TPCs but rather to small molecular weight binding proteins that associate with TPCs (65)(66)(67).…”
Section: Controversymentioning
confidence: 99%